2016
DOI: 10.1177/0269215516637202
|View full text |Cite
|
Sign up to set email alerts
|

Pilates exercise training vs. physical therapy for improving walking and balance in people with multiple sclerosis: a randomized controlled trial

Abstract: Pilates is a possible treatment option for people with multiple sclerosis in order to improve their walking and balance capabilities. However, this approach does not have any significant advantage over standardized physical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 36 publications
4
61
0
5
Order By: Relevance
“…Newell 2012 showed the Pilates exercise have potential to improve gait and sway parameter [26] in older adults. Therefore, the results of the present study are in agreement with the results of previous studies that PBCS exercises have significant effect on gait [29, [36][37][38][39].…”
Section: Discussionsupporting
confidence: 93%
“…Newell 2012 showed the Pilates exercise have potential to improve gait and sway parameter [26] in older adults. Therefore, the results of the present study are in agreement with the results of previous studies that PBCS exercises have significant effect on gait [29, [36][37][38][39].…”
Section: Discussionsupporting
confidence: 93%
“…Mokhtari in a study of 30 elderly females stated that 12 weeks of mat Pilates exercises developed balance features and reduced the risk of falling in the elderly (Mokhtari et al, 2013). Kalron performed 12 weeks of Pilates exercises with 45 multiple sclerosis patients and found the physical fitness parameters of balance and flexibility had developed at the end of 12 weeks (Kalron et al, 2017). In our study, 2 days per week Pilates exercise developed all parameters apart from shoulder mobility.…”
Section: Discussionsupporting
confidence: 57%
“…Previous research has dealt with topics like the effects of long-term Pilates exercises on mobility, stabilization and balance parameters, and rehabilitation after low back pain and sporting injuries (Bryan & Hawson, 2003;Phrompaet et al, 2011;Pata et al, 2014;Cruz-Dí az et al, 2015;Kalron et al, 2017;Peterson & Haladay, 2018). Acute studies have compared the FMS scores of different ages and groups with swimming, gymnastics, football and sedentary activity (Bond et al, 2017;Sahin et al, 2017;DORREL et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That said, regarding studies on the use of Pilates, only three included climacteric women in their samples (17,18) and in one study an analysis of the specific effects of a Pilates intervention was not performed, as it comprised of an analysis on the possible effects on QOL in practitioners of Pilates, aerobics and strength training (17). The study by kalron showed that no significant differences were observed in QOL of women who did Pilates exercise and walking (19). Although there are a few studies on the relationship between the Pilates method and quality of life (12,(20)(21)(22), other studies have focused on other aspects that could contribute to improving QOL in climacteric women (23).…”
Section: Introductionmentioning
confidence: 99%